Blue Rubber Bleb Nevus Syndrome with Long-Term Follow-Up: A Case Report and Review of the Literature. (25th November 2018) - Nakajima, Hideaki; Nouso, Hiroshi; Urushihara, Naoto; Fukumoto, Koji; Yamoto, Masaya; Miyake, Hiromu; Sekioka, Akinori; Nomura, Akiyoshi; Yamada, Yutaka
Abstract : Blue rubber bleb nevus syndrome (BRBNS) is a rare disease in which venous malformations (VMs) involve any body organ, most commonly the skin and the gastrointestinal (GI) tract. Treatment of BRBNS aims at preserving the GI tract as much as possible. Although there are several dozen case reports about BRBNS that describe short-term clinical courses, a few provide an account of long-term clinical course. Here, we report a case of BRBNS in a girl that required multiple abdominal surgeries due to the GI VMs and a recurrence at an interval of 14 years. The preferred approach for gastrointestinal VMs involves the complete resection of all lesions without residual VMs. It is important to bear in mind the possibility of delayed recurrence of GI VMs after surgical or endoscopic treatment.